Analisis strategi pemasaran perpajakan pada Kantor Pelayanan Pajak Pratama Yogyakarta - KOHARUDDIN, Abdillah ([Yogyakarta] : Universitas Gadjah Mada, 2008)
Marketing became a right planning tool for public sector to fulfill society needs and offering values to citizens. Public sector can adopt marketing mindset and marketing principles into mission, objectives, goals and problem solving. The background of this research are reality problem on performance indicators that are target realization, tax ratio, tax coverage ratio and increasing demand of improving services quality. The objective of this research are to recommend a new marketing strategy. This study used qualitatif methode, which try to find out the comprehensive illustration about marketing strategy. The research was done in Yogyakarta Taxpayer Office with operation area in Yogyakarta City. SWOT analysis used to find out strategic factors, strategic issues, and finally to recommend a new strategy. This researh concludes recommendation a marketing mix strategy in Yogyakarta Taxpayer Office. Product strategy, we suggest to develop tax services programme, i.e., to learn taxpayers profil and formulating a Taxpayers’ Charter. Accomplishment good corporate governance programme and complaint centre programme, formulated to increasing trust of taxation system. Distinction enforcement activity according to the degree of taxpayer compliance, was recommended in price strategy. Distribution channels strategy, we suggest to improving digitalize services and optimalitation of information system. Promotion strategy, we suggest to develop effective communication with stakeholder, i.e., public relation; workshop and taxations’ training; socialization tax for development; and tax go to school/campus.